270. SAFETY AND EFFICACY OF PREOPERATIVE FOLFOX FOR PATIENTS WITH RESECTABLE ESOPHAGEAL SQUAMOUS CELL CARCINOMA WHO ARE NOT CANDIDATES FOR CISPLATIN. (24th September 2022) - Kadono, Toru; Yamamoto, Shun; Ohara, Akihiro; Itoyama, Mai; Yokoyama, Kazuki; Honma, Yoshitaka; Ishiyama, Koshiro; Oguma, Junya; Daiko, Hiroyuki; Kato, Ken
Abstract: The standard preoperative treatment for resectable locally advanced esophageal squamous cell cancer (LAESCC) in Japan is a cisplatin (CDDP)-containing chemotherapy. However, patients with renal or cardiac dysfunction and elderly patients are not candidates for CDDP because of renal toxicity and the need for hydration. Oxaliplatin, 5-fluorouracil, and leucovorin (FOLFOX) therapy causes less renal toxicity and does not require hydration. We evaluated the preoperative FOLFOX therapy in patients who are unsuitable for CDDP remains unknown. The subjects of this retrospective study were histologically confirmed LAESCC patients unsuitable for CDDP because of an age ≥ 75 years or a creatinine clearance (CCr) <60 mL/min, or cardiac dysfunction who received preoperative FOLFOX therapy at our hospital between 2019 and 2021. Supraclavicular lymph node metastasis was considered resectable. Preoperative FOLFOX therapy (oxaliplatin 85 mg/m2, leucovorin 200 mg/m2, and 5-fluorouracil 400 mg/m2 [bolus] plus 2400 mg/m2 [continuous] every 2 weeks) was administered for 3 or 4 courses. We evaluated adverse events during preoperative chemotherapy (CTCAE version 5.0), complete resection rate, and histopathological response. Thirty-five patients were eligible for inclusion in the study (median age 77 years [range, 65–89]; performance status 0/1, 40%/60%; clinical stage I/II/III/IVB [only supraclavicular lymph node], 11%/29%/57%/3%). The reasons for selecting FOLFOX were renal dysfunction (74%), age ≥ 75 years (69%), and cardiac dysfunction (17%). Four patients (11.4%) discontinued chemotherapy because of progression (n = 2), febrile neutropenia (n = 1), or neutropenia (n = 1). The most common grade ≥ 3 adverse events were neutropenia (60%) and leucopenia (29%). 31 patients underwent surgery. The complete resection rate was 87% (27/31) and the pathological complete resection rate was 16% (5/31). There were no treatment-related deaths. Preoperative FOLFOX therapy was well tolerated and showed promising short-term efficacy in patients with resectable LAESCC who were not candidates for CDDP.